2017
DOI: 10.1002/jcb.26138
|View full text |Cite
|
Sign up to set email alerts
|

Gingerenone A Attenuates Monocyte‐Endothelial Adhesion via Suppression of I Kappa B Kinase Phosphorylation

Abstract: During the early stages of atherosclerosis, monocytes bind and migrate into the endothelial layer, promoting inflammation within the aorta. In order to prevent the development of atherosclerosis, it is critical to inhibit such inflammation. The therapeutic effects of ginger have been investigated in several models of cardiovascular disease. However, although a number of previous studies have focused on specific compounds, the mechanisms of action responsible remain unclear. Here, we investigated five major com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In addition to chemokines, cell adhesion molecules play a major role in leukocyte migration to infl amed organs. Zerumbone and gingerenone inhibit the expression of ICAM-1 and VCAM-1 [97,98].…”
Section: Concerningmentioning
confidence: 99%
“…In addition to chemokines, cell adhesion molecules play a major role in leukocyte migration to infl amed organs. Zerumbone and gingerenone inhibit the expression of ICAM-1 and VCAM-1 [97,98].…”
Section: Concerningmentioning
confidence: 99%
“…On the other hand, SIRT-3 and SIRT6 overexpression reduced atherogenesis in mice. The deletion of TNF-α/β [ 26 ] and MCP-1 genes [ 27 ] prevented vascular inflammation, adhesion molecules expression, collagen (I, III), ECM protein deposition and AS plaque formation by inhibiting aforesaid pathways in mice [ [28] , [29] , [30] , [31] ]. Interestingly, overexpression of P2Y2 nucleotide receptor (P2Y2R), which regulates vascular inflammation and AS plaque formation, correlate with increased production of vascular adhesion molecule and inflammation by activating TNF-β/Akt/NF-κB pathway in the AS susceptible region in the aorta.…”
Section: Abnormalities In Dna and Histone In Asmentioning
confidence: 99%
“…Several studies also suggested that consumption of ginger and its major bioactive constituents are associated with decreased risk of cardiovascular diseases (CVD), such as hypertension and atherosclerosis. [5,6] Ginger was reported to be used for the prevention of hypertension, which is supported by studies showing the inhibition of angiotensin-1-converting enzyme by ginger[7] as well as the inhibition of angiotensin II type 1 receptor (AT 1 ) activation by 6-gingerol. [8] Ginger and its major bioactive constituents also led to a significant reduction in platelet aggregation, which plays a central role in hemostasis and thrombosis.…”
Section: Introductionmentioning
confidence: 99%